Penerapan Dan Pemanfaatan E-Office Pada Kantor Sekretariat Daerah Kota Salatiga - Noplyantri Narsen; Agus Sugiarto (Universitas Bina Sarana Informatika, 2022)
Electronic office is all work related to office management which is done electronically with communication equipment and information systems. The purpose of this study was to analyze the application, benefits, and constraints and challenges of the electronic office at the Salatiga City Regional Secretariat. The method used is descriptive with a qualitative approach. Data collection techniques were carried out by means of observation, interviews, and also documentation studies. Data analysis activities are carried out through the stages of data condensation, data presentation, and drawing conclusions. The results show that the Salatiga City Regional Secretariat office has implemented the use of electronic office. In the process of implementing the electronic office, the initial steps and components as well as the planning stages of the electronic office are very important and needed to simplify the implementation process. There is also an electronic office that has different benefits according to each section in the Salatiga City Regional Secretariat office. However, there are also obstacles and obstacles that result in the process of implementing and using electronic office at the Salatiga City Regional Secretariat office not yet functioning and playing an optimal role. The implication of the application and use of the electronic office at the Salatiga City Regional Secretariat is to assist employees in completing work effectively and efficiently.